Standards for local public health services: where stand the states? - Schaefer, M (1985)
Of the 47 states that participated in a 1983 survey of State Health Departments, 30 were found to have public health standards in place or started. Most states' standards emphasize the range of services to be provided, but substantial variations were found in how standards are formulated, adopted, and used by state and local agencies.